The Bonding of Soft Lining Materials to The Denture Base: Meta-Analysis - Nuran Yanıkoğlu; Büşra Tosun (Selcuk Dental Journal)
Background: One of the biggest disadvantages of soft lining materials is that they deform over time and cause ruptures and fractures in the bonding with the denture base. To overcome these problems, the factors that weaken the bonding should be determined and measures should be taken accordingly. The aim of this study is to elucidate the factors affecting the bonding of soft lining materials to the denture base, in terms of dental base and soft lining materials, surface treatments and retention agents. Methods: The keywords 'soft lining materials, dental base, bond strength' were written and searched using PubMed/Medline databases, and as a result, 54 research articles related to the current study were evaluated. Each article was classified in terms of the type of denture base and soft lining material, methods of surface treatment, retention agents, and bond strength. Results: While retention in saliva and water bathing decreased the shear bond strength compared to the group without any retention agent, the application of cleaning agents increased the shear bond strength. The tensile bond strength varied according to the surface treatments, and the laser application showed the highest tensile bond strength. In terms of peel strength, the heat-treated group and the laser with chemical treatment applied group showed lower bond strength than the mechanical treatment and soaked group. Conclusion: It was concluded that cleaning agents, laser application and mechanical treatments increased the tensile, shear and peel strength.